Jokowi's Political Dynasties: Impact and its Comparison to Nehru-Gandhi Dynasties - Kiki Novilia; Arie Purnama; Andy Corry Wardhani; Nanang Trenggono (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
This research focuses on the Jokowi political dynasty that is now underway. The dynasty was marked by the advancement of Jokowi's eldest son, Gibran Rakabuming, as Mayor of Solo some time ago, followed by Jokowi's son-in-law, Bobby Nasution, becoming Mayor of Medan. A few days ago, Jokowi's youngest son, Kaesang Pangarep, was predicted to run in the Depok regional election. The participation of Jokowi's son and son-in-law as regional heads establishes an unprecedented milestone in the annals of Indonesian political dynasties. Because there has never been a similar case since independence, this condition has caused various negative impacts on the Indonesian nation. It starts from opening opportunities for corruption and the difficulty of regenerating new political cadres to injuring democracy. Relatives sitting in strategic seats will perpetuate the dynasty and protect each other. Thus, it will be challenging to prioritize the people because family interests hinder it. In addition, this paper will include a review of the Nehru-Gandhi dynasty of India as a comparison. The dynasty was chosen because it has a long history that lasts for generations. This phenomenon captured Indonesian political dynasties. Carrying the type of qualitative research, this research used various literature reviews as its basis. Hopefully, this research can be the mainstay of literacy for various parties facing the upcoming 2024 political year.